Investigating the role of Gfi1s/1b transcription factors in the HSC-derived thrombocyte lineage - Jaddah, Mariam (2024)
Blood formation, haematopoiesis, during development occurs in multiple waves, and it starts from mesodermal cells which give rise to primitive wave blood cells and endothelial cells (ECs) which become hemogenic endothelium (HE). Haematopoietic stem cells (HSCs) emerge from HE in the ventral wall of the dorsal aorta (vDA). Growth factor independence 1aa (gfi1aa) is expressed in HE, and in our lab, we found that HSC formation is not affected in the gfi1aa mutant. However, there was upregulation of its paralogue expression, gfi1ab, in the ventral wall of the dorsal aorta (vDA) in the absence of Gfi1aa, suggesting a functional redundancy between Gfi1aa and Gfi1ab. Here, zebrafish embryos that were double homozygous for the gfi1aa and gfi1ab mutants were used to determine whether HSC emergence is affected in the absence of both proteins. Whole mount in situ hybridisation experiments revealed that haematopoietic stem cells (HSCs) were still able to emerge from the ventral wall of the dorsal aorta (vDA), but the number of definitive blood cells that seed the subsequent haematopoietic tissues was severely reduced. The reduction in Hematopoietic stem and progenitor cells (HSPCs) was confirmed using the CD41: GFP+ line which expresses low levels of GFP in definitive progenitors and increasing levels as they turn into thrombocytes. Transgenic embryos that were homozygous for mutant gfi1aa and gfi1ab were found to carry fewer GFP+ cells, suggesting a lower number of emerging hematopoietic stem and progenitor cells (HSPCs). In the gfi1aa single mutant and gfi1aa/ab double mutant, gfi1b was not expressed in the vDA of these embryos at any point during the emergence of hematopoietic stem and progenitor cells (HSPCs), unlike gfi1ab.Further loss of Gfi1b did not abrogate definitive HSPCs formation but expanded the myb+ blood cell population in the caudal hematopoietic tissues, CHT, when depleted in combination with Gfi1aa. In addition, using the CD41: GFP+ line with the third homologs mutant embryos, gfi1b, thrombocytes failed to enter circulation. Data from the adult kidney marrow of the gfi1b mutant showed that the fraction of CD41+ cells was significantly increased, while peripheral blood examination revealed thrombocytopenia. These data suggest that thrombocytes are held back into the kidney marrow. Further analysis of kidney marrow (KM) using gata1 and cd41 double transgenic fish revealed the accumulation of transcriptionally misprogrammed mature thrombocytes. In addition, thrombocytes in embryos and adults were functionally impaired in gfi1b qmc554 hom mutant carriers. To gain a deeper understanding of the molecular programming of Gfi1b-depleted thrombocytes, bulk RNA-sequencing analysis was performed. RNA-Seq data have shown upregulation of adhesion, endothelial, and globin expression genes and downregulation of cytoskeleton gene expression in Gfi1b depleted thrombocytes and thrombocyte progenitors.